Great Britain Smart Meter Role-Out Programme:Appraisal of Cost & Benefits for Energy Suppliers - Lu, Man Man (2010)
By the end of 2008, UK government announced its intention to make smart meter roll-out a mandate. Energy suppliers have been given the instruction to have smart meter installed in all household in Great Britain by 2020, and are expected to bear substantial costs for this programme. The objective of this study is to discuss the costs and benefits involved in this programme from suppliers’ perspective by identifying the cost and benefit (the cost reduction part which is quantifiable) items involved and come up with the net cost (the difference between expected cost and cost reduction). The intangible benefits that can’t be quantified are then discussed separately. The net cost for suppliers in a twenty-year horizon is substantial, especially during the peak period of roll-out. The procurement cost and installation cost are the most important parts. Variables like access rate will impose significant impact on the installation cost, for suppliers, so it is crucial to keep a high access rate to avoid labour force waste and control the installation cost. To acquire high access rate, suppliers should obtain certain degree of customer engagement level by develop an effective customer engagement strategy, which can be referred to the group report “Great Britain Smart Meter Roll-out Programme: Customer Engagement Strategy for E.ON”.